PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL UNTUK MENGHADAPI ISU-ISU STRATEGIS TERKINI DI ERA DIGITAL - Riswandha Ipnu Nawawi; Fisman Bedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education is an important aspect in forming quality individuals, especially amidst the complex challenges that arise in the digital era. In this context, a character education approach based on local wisdom offers relevant and holistic solutions in dealing with current strategic issues. This research explores the importance of integrating local values into character education as a way to strengthen cultural identity, improve social and moral skills, and face complex social challenges in the digital era. Through in-depth interviews, participant observation, and document analysis, this research identified that local wisdom-based character education requires strong support from various stakeholders, including teachers, parents, schools, and local communities. Collaboration between educational institutions and local communities is key to ensuring the relevance of local values to current social and economic needs. The results of this research provide insight into how character education based on local wisdom can be an effective strategy in preparing the younger generation to face the challenges of the times and build a better future.